Trends in a Cohort of HIV-infected pregnant women in Rio de Janeiro, 1996-2004 Tendências temporais observadas em uma coorte de gestantes infectadas pelo HIV acompanhadas no Rio de Janeiro de 1996 a 2004 - Guilherme Amaral Calvet; Esaú Custódio João; Karin Nielsen-Saines; Cynthia Braga Cunha; Jacqueline Anita Menezes; Marcos Machado d'Ippolito; Maria Letícia Santos Cruz; Ezequias Batista Martins; Sônia Maria Santos Silva; Adriana Ferreira Medeiros; Haroldo José Matos (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2007)
OBJECTIVE: To describe trends in sociodemographic, immunological and virological profiles and interventions to decrease the risk of mother-to-child HIV transmission. METHODS: Retrospective cohort study conducted at a tertiary institution in Rio de Janeiro, Brazil from January 1996 to December 2004. Analysis was performed by stratification in three time periods: 1996-1998 (P1), 1999-2001 (P2) and 2002-2004 (P3). RESULTS: In 9 years, 622 pregnancies occurred. Complications included: maternal mortality 0.3%, stillbirths 2.5%, miscarriages 0.6%, neonatal mortality 1.1%, prematurity 9.9%, low birth weight (LBW) 16.5%, congenital malformations 2.2%. The number of HIV-infected pregnant patients grew threefold over time reflecting increased prevalence of disease and patient identification. HIV diagnosis before pregnancy increased from 30% in P1 to 45% in P3. The proportion of pregnant women receiving highly active antiretroviral therapy increased from none (P1) to 88% (P3) with a significant trend towards women delivering at undetectable viral loads in later years despite a higher frequency of advanced disease. Scheduled cesarean deliveries increased from 35% in P1 to 48% in P3. Perinatal transmission rates were 2.4% with a decline from 3.5% in P1 to 1.6% in P3. Neonatal outcomes tended to remain constant or improve with time. A slight rise in LBW and congenital malformations were observed. CONCLUSIONS: During the observational period, HIV+ pregnant women presented with more advanced disease and lower socio-economic status. However, improved management of HIV-infected patients (associated with increased identification and increased availability of treatment) resulted into very low transmission rates similar to those of developed countries with overall improvement of patient outcomes. OBJETIVOS: Descrever as tendências temporais nas características sociodemográficas, imunológicas e virológicas e as das condutas utilizadas para reduzir o risco da transmissão mãe-filho do HIV. MÉTODOS: Estudo de coorte retrospectivo em uma instituição de saúde terciária no Rio de Janeiro de janeiro de 1996 a dezembro de 2004. A análise utilizou a estratificação em três períodos de tempo: 1996-1998 (P1), 1999-2001 (P2) e 2002-2004 (P3). RESULTADOS: Em 9 anos, 622 gestações foram acompanhadas. As complicações foram: mortalidade materna 0,3%, natimortos 2,5%, abortos 0,6%, mortalidade neonatal 1,1%, prematuridade 9,9%, baixo peso ao nascer (BPN) 16,5%, malformações congênitas 2,2%. O número de gestantes HIV positivo triplicou ao longo do tempo, refletindo o aumento da prevalência da doença e a melhor identificação das pacientes. O diagnóstico da infecção pelo HIV antes da gestação aumentou de 30% em P1 para 45% em P3. A proporção de gestantes recebendo o tratamento combinado potente aumentou de zero em P1 para 88% em P3 com uma tendência significativa a ter uma carga viral abaixo do limite de detecção no parto nos últimos anos apesar de uma maior proporção de pacientes com doença mais avançada. O índice de cesarianas eletivas aumentou de 35% em P1 para 48% em P3. A taxa de transmissão perinatal global foi de 2,4% caindo de 3,5% em P1 para 1,6% em P3. Os desfechos neonatais tenderam a permanecer constantes ou a melhorar ao longo do tempo. Um discreto aumento dos índices de BPN e de malformações congênitas foi observado. CONCLUSÕES: Ao longo do período de estudo aumentou a proporção de gestantes HIV positivo com doença mais avançada e com padrão socioeconômico mais baixo. Por outro lado, a melhora da abordagem terapêutica dos pacientes infectados pelo HIV, associada a uma maior detecção de casos e maior acesso ao tratamento, resultou em uma redução da taxa de transmissão igualando-se à observada em países desenvolvidos com melhora concomitante de outros desfechos.